Combing location-aware applications with in-situ actors performances - Alconada Verzini, Federico Martín; Tonelli, Juan Ignacio; Challiol, Cecilia; Lliteras, Alejandra Beatriz; Gordillo, Silvia Ethel (2015)
In this paper we present a model to define location-aware experiences having its different aspects (contents, location, etc) decoupled one from another. We have created an application following this model, which is also combined with actors’ performances. This application defines three relevant locations inside a specific building. By reading a QR-code the user indicates that he/she has arrived at one of those locations. In that moment, the application triggers some questions related to the actors’ performances. Hence, the user is required to see all the plays in order to be able to answer such questions. The application assists the user in moving throughout the different locations. We present the evaluation of this application and then we discuss interesting aspects that have shown up as a result of the in-situ evaluation of this application.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
ACM Conference on Hypertext and Social Media (26ta : 2015 sep. 1-4 : Güzelyurt, Turquía). NHT Proceedings of the 2015 Workshop on Narrative & Hypertext, pp. 27-31.
Keywords: APLICACIONES; COMPUTACIÓN MÓVIL; ANÁLISIS DE RENDIMIENTO